2009
DOI: 10.1111/j.1365-2567.2008.03004.x
|View full text |Cite
|
Sign up to set email alerts
|

Virulence, immunopathology and transmissibility of selected strains ofMycobacterium tuberculosisin a murine model

Abstract: Summary After encounter with Mycobacterium tuberculosis, a series of non‐uniform immune responses are triggered that define the course of the infection. Eight M. tuberculosis strains were selected from a prospective population‐based study of pulmonary tuberculosis patients (1995–2003) based on relevant clinical/epidemiological patterns and tested in a well‐characterized BALB/c mouse model of progressive pulmonary tuberculosis. In addition, a new mouse model of transmissibility consisting of prolonged cohousing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 26 publications
4
77
1
3
Order By: Relevance
“…Animal models that take advantage of an identical genetic background, and therefore a uniform host immune response, have given insight regarding the contribution of strain genetic diversity to the outcome of the infectious process (7,20). It is currently accepted that genetically different M. tuberculosis strains produce markedly different immunopathological events in isogenic mice (4,18).…”
mentioning
confidence: 99%
“…Animal models that take advantage of an identical genetic background, and therefore a uniform host immune response, have given insight regarding the contribution of strain genetic diversity to the outcome of the infectious process (7,20). It is currently accepted that genetically different M. tuberculosis strains produce markedly different immunopathological events in isogenic mice (4,18).…”
mentioning
confidence: 99%
“…Several studies have reported heterogeneity in the cytokine response induced by various genotypes of MTB [5,20]. Strains of modern lineages (lineage 2, 3 and 4) were shown to induce lower levels of proinflamatory cytokines when compared with ancient lineages (lineage 1) [10].…”
Section: Discussionmentioning
confidence: 99%
“…It was traditionally assumed that MTB was genetically homogenous because early studies revealed very low levels of DNA sequence variation. However, after the discovery of molecular typing methods, it is now well known that different types and subtypes of MTB do exist and that genotype might be associated with differences in virulence, antibiotic susceptibility, relapse and prevalence of disease [3][4][5][6]. Several recent studies, including ours, suggest that phylogenetic diversity of the strains is also associated with diversity in biological response of the host [7].…”
Section: Introductionmentioning
confidence: 99%
“…Our transmissibility model is based on long co-housing between infected and healthy mice [23]. This model was used to determine whether or not AdGM-CSF treatment was able to prevent infection of healthy mice co-housed with animals infected with moderate (H37Rv) or highly virulent (Beijing 900-1000) strains.…”
Section: Effect Of Transgenic Gm-csf Expression On the Transmission Omentioning
confidence: 99%
“…The transmissibility experimental model has been described previously [23]. Five BALB/c mice infected (2·5 ¥ 10 5 bacilli) with Mtb H37Rv or highly virulent Beijing strain 9001000 were co-housed in the same micro-isolator from the first day of infection with five healthy non-infected BALB/c mice (contacts), which received AdGM-CSF (1 ¥ 10 8 pfu IT) by the i.t.…”
Section: Mtb Transmissibility Experimental Model In Balb/c Micementioning
confidence: 99%